Characterization of Flower’s Color based on CHS Gene Structure in Phalaenopsis ‘OX Queen’ and Dendrobium ‘Cheddi Jagan’ Orchids - Hanifa, Yumna Rahmadias; Gildantia, Elke; Kasi, Pauline Destinugrainy; Purwantoro, Aziz; Semiarti, Endang (Journal of Tropical Biodiversity and Biotechnology, 2024)
Orchids (Orchidaceae) are ornamental plants known for their high aesthetic value attributed to the shapes, colours, and fragrances of their flowers. Two types of hybrid orchids with attractive flowers, namely the Phalaenopsis 'OX Queen' orchid and the Dendrobium 'Cheddi Jagan' boast attractive flowers were used in this research, because of the beauty of its flower colour. The objective of this research is to characterise the morphology of flower colour and CHS (Chalcone Synthase) gene content that induces flower colour. The method used in this research analyzing the flower’s colour by using the RHS (Royal Horticultural Society) colour chart and molecular analysis by DNA genomic isolation and PCR amplification of gDNA for CHS gene specific primers. The results showed that purple colour is observed through the RHS, with P. 'OX Queen' coded as Deep Purple Pink (N73A) and D. 'Cheddi Jagan' coded as Strong Reddish Purple (N72C). The CHS gene can be amplified in P. ’OX Queen’ 1,287 bp and D. ’Cheddi jagan’ 3,731 bp. In both orchids, the results of amplification showed CHS motifs with conserved domains PLN03172 and PLN03170. The research results show that there is a significant difference in the morphology of the flowers of orchids. Purple colour is observed through the RHS, with P. 'OX Queen' coded as N73A and D. 'Cheddi Jagan' coded as N73C. The results showed that gDNA can be isolated by using CTAB method according to Murray and Thomson, and the CHS gene can be amplified by using CHS primers, resulting 1200 bp of P. 'OX Queen' and 2500 bp for D. 'Cheddi Jagan'. Through this study, preliminary data is expected to be obtained for future research, which is the formation of variegated flowers through editing the CRISPR/Cas9 genome in the CHS gene. This research is intended to support further studies on the formation of variegated flower patterns in P. 'OX Queen' and D. 'Cheddi Jagan’, focusing on the CHS gene using CRISPR/Cas9 technique.